Evaluation of Ma'had Al-Jami'ah Program in Developing Students’ Tahsin Skill - Nurfadilla, Nurfadilla; Muhaemin, Muhaemin; Masruddin, Masruddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
One of Ma'had al-Jami'ah's missions is to produce students adept at reading and correctly writing the Koran. However, the implementation of the Ma'had al-Jami'ah program is still considered not optimal in improving students' skills because there is a gap between the concept of the Tahsin al-Qur'an learning program and the situation that occurs in the field. This research aims to present comprehensive and in-depth information about the evaluation results of the Ma'had al-Jami'ah program in developing students' Tahsin skills. This research uses the CIPP (Context, Input, Process, Product) model evaluation research developed by Stufflebeam. Interviews and document study carried out data collection. The subjects in this research were the Head of the Ma'had Al-Jami'ah Unit, Ma'had Program lecturers, and students. Data analysis uses the Milles and Huberman model. Based on the evaluation carried out on the Ma'had Al-Jami'ah IAIN Palopo program. The results were that the IAIN Palopo Ma'had al-Jami'ah Program, in improving students' Tahsin skills, was considered very good overall. With each aspect: 1) the context aspect is in the very good category by meeting four indicators; 2) the input aspect is in the good category by fulfilling three of the four categories; 3) the process aspect meets four indicators, so it is included in the very good category; and 4) product aspects are also in the very good category by meeting three indicators.